Tanzania: Cost effective options for inclusive and sustainable development - Aragie, Emerta A.; Thurlow, James; Xu, Valencia Wenqian; Jones, Eleanor (International Food Policy Research Institute, 2025)
In this policy brief, we present research findings of a systematic evaluation and ranking of investment options for Tanzania’s agrifood system based on their cost-effectiveness in achieving multiple development outcomes, including agrifood gross domestic product (GDP) growth, agrifood job creation, poverty reduction, declining rates of undernourishment, and lowering diet deprivation. Additionally, the study assesses their environmental footprint, focusing on water consumption, land use, and emissions. Investments in extension and advisory services on livestock are shown to be the most cost-effective in expanding agrifood GDP and jobs. We also find that targeting SME processors generates stronger impacts on jobs, while extension services in agronomy are particularly cost-effective in fostering growth. Similarly, investing in extension services in agronomy and livestock, along with support to SME processors, yields significant gains in social outcomes, though with varying effects on poverty, hunger, and diet quality. However, many cost-effective investments have relatively high environmental footprints, highlighting potential tradeoffs. The study further reveals shifts in the cost-effectiveness ranking of investment options over time and when extreme production shocks occur.